TRADISI MAMOKKOT RUMAH BAYU DI MASYARAKAT SIMALUNGUN: KAJIAN TRADISI LISAN - Like Erina Tumangger; Immanuel Silaban; Immanuel Bintang Cristopher Batubara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Mamokkot Rumah Bayu tradition is an oral cultural heritage of the Simalungun people, passed down from generation to generation and still holds significant value in the social life of the Simalungun people. This tradition is carried out as a form of inauguration of the Rumah Bayu or traditional house, accompanied by various stages, traditional ceremonies, traditional speeches, prayers, advice, and symbolic expressions conveyed orally. This study aims to examine the Mamokkot Rumah Bayu tradition as part of the Simalungun oral tradition and to understand its meaning and socio-cultural functions. The Mamokkot Rumah Bayu tradition contains various forms of oral tradition, such as umpasa (incantations), traditional advice, prayers, and symbolic communication, which serve as a medium for conveying cultural values, honoring ancestors, and strengthening social ties within the community. Furthermore, this tradition also reflects the values ​​of mutual cooperation, solidarity, respect, and the role of tolu sabundulan (social bonds) in Simalungun traditional life. The Mamokkot Rumah Bayu tradition is beginning to undergo changes, particularly in the use of traditional language and the completeness of the ceremonial stages. Nevertheless, this tradition is still maintained by the community as part of their cultural identity and ancestral heritage, possessing historical and educational value. Therefore, the preservation of oral traditions in the mamokket rumah bayu (house of bayu) is necessary to ensure that Sumalungun cultural values ​​are maintained and recognized by the younger generation.